Current Rehabilitative Concepts in Ear Nose and Throat Department, University of Medical Sciences Teaching Hospital (UNIMEDTH): Challenges Encountered - Akpalaba I.O.,; Olarinoye T.O.,; Ikong M.A.,; James. R. O, (Archives of Current Research International, 2024)
Introduction: Unaddressed communication disorders are multidimensional, affecting individuals physiologically, psychologically and emotionally. The quality of life of these individuals can be improved with rehabilitative measures, justifying this study. The study therefore aims to assess the impact of rehabilitation on these patients, determine the challenges and proffer possible solutions. Methods: Eighteen months prospective study on audiological and speech disorders among ENT patients in the University of Medical Sciences Teaching Hospital, Ondo State, from April 2021 to September 2022 was carried out. History was taken, general examination and full E.N.T. examinations were done. Those with audiological disorders from canal blockage due to foreign bodies, debris and impacted wax had ear syringing. Others with persistent audiological condition were further evaluated and treated accordingly, with Hearing Aids trial and fitting inclusive. Patients with speech disorder had speech therapy after baseline audiological screening. Data were represented in tables and figures. P value < 0.05 was statistically significant. Results: 930 patients presented at the ENT clinic. 537 (57.74%) females and 393 (42.26%) males. Of this, 405 (43.55%) patients had audiological conditions while 23 (2.47%) had speech disorders. Impacted wax, tinnitus, hearing loss, foreign body in the ear and delayed speech development were commonest. 297 had syringing while 105 patients were further evaluated. 369 of 405 patients were successfully rehabilitated. 3 stroke patients had good speech recovery. Predominant challenges encountered were unavailability of instruments and uncooperativeness of elderly patients. Weekly savings and incorporation of dedicated relatives for home therapy ensures solutions respectively. Conclusion: Rehabilitation in E.N.T., though gradually progressive, is beneficial. The guiding concept is patience.